2000
DOI: 10.1007/s11664-000-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photoluminescence study of ZnSe quantum dots

Abstract: Special Issue Paper 173Quantum dots (QDs) have received much attention because of their potential applications in optical and opto-electronics devices. 1,2 Various ways of producing QDs have been demonstrated. 3-5 Self-organized QDs attracted the most attention because of their nondestructive and non-growth-interrupted nature. InAs quantum dots on GaAs 6 and Ge quantum dots on Si 7 are well-known examples. These quantum dots were found to grow under the Stranski-Krastanov mode: a layer was first grown in two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…It appears that when the growth time is long, the small quantum dots merge together to form a big cluster, and the density of the smaller dots actually decreases. In the previous study we found that PL intensity decreases and sometimes disappears completely with increasing ZnSe growth time [4][5][6]. This is consistent with the SEM results which show that as the growth time increases, the density of small QDs that are responsible for the high e cient light emission decreases with growth time.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…It appears that when the growth time is long, the small quantum dots merge together to form a big cluster, and the density of the smaller dots actually decreases. In the previous study we found that PL intensity decreases and sometimes disappears completely with increasing ZnSe growth time [4][5][6]. This is consistent with the SEM results which show that as the growth time increases, the density of small QDs that are responsible for the high e cient light emission decreases with growth time.…”
supporting
confidence: 89%
“…1(c), when the growth duration time is 10 s, large clusters show up and are the dominant feature of the surface. These high-resolution SEM pictures provide the evidence we claimed previously that it is not a S-K growth, or a layer plus island growth, instead, the growth is a Volmer-Weber mode, or direct island growth [4][5][6][7]. An important feature to be noted from these pictures is that when the growth time is short, the QD size is also small.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Core is made up of a semiconducting material (PbSe) which is coated with the lattice matched shell material (CdSe) in order to improve its optical properties. These core/shell materials show novel optical properties better than the bare quantum dots [13][14][15]. PbSe related colloidal core/shell heterostructures have been investigated for optoelectronic applications [16].…”
Section: Introductionmentioning
confidence: 99%